Florida's Renewable Forest Resources - Douglas R. Carter; Eric J. Jokela (EDIS, 2003)
Florida's forests are a vigorous and dynamic resource, covering 16.2 million acres or 47% of Florida's total land base, contributing over $7 billion annually to the state's economy. These forests are desired by a diversity of clientele for a multitude of market and nonmarket goods and servicesThis document is CIR1433, one of a series of the School of Forest Resources and Conservation, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. First published December 2002.